Memotret Strategi Komunikasi Pemasaran Terintegrasi Pada Industri Fashion - Andriansyah Bari (Jurnal Manajemen dan Bisnis, 2020)
ABSTRACTSaddap Leather Goods is a company which engaged in fashion especially leather products. As a newly established company, Saddap faces several problems from some divisions, particularly in the marketing division. It is found that brand awareness of Saddap is still considered low. This can be seen from the small number of follower on Instagram. This study aims to find the problem in Saddap by conducting the internal analysis. This analysis consists of SWOT Analysis and TOWS Analysis. The data in this study were obtained through interviews with six informants which consists of Saddap excisting consumer and potential consumer. The data were also obtained through observation, literature (library research), and documentation. From this study it can be concluded that Saddap was facing ineffectiveness of previous marketing activity. To fix this problem, Saddap uses marketing communication tools through the Integrated Marketing Communication. Marketing communication tools proposed by Saddap are Advertising, Sales promotion, Redesign of packaging, Personal Sales, Trade shows and Direct Marketing. This research proposed the short and long term marketing activity